Investor Behavior in Cryptocurrency Market in Indonesia: The Role of Trust, Regulation, Digital Access and Risk Perception Through Psycological Empowerment - Putra Jayani, Angga; Adrianto, Fajri; Hamidi, Masyhuri (DINASTI RESEARCH, 2025)
This study examines the determinants of investor behavior in Indonesia’s cryptocurrency market, focusing on trust, regulation, digital access, and risk perception, with psychological empowerment as a mediating variable. Motivated by the rapid growth of crypto adoption in Indonesia alongside issues of volatility, regulatory uncertainty, and varying levels of digital literacy, the research aims to identify how these factors influence investment decisions. A quantitative explanatory design was applied, using a structured online questionnaire distributed to 150 active Indonesian cryptocurrency investors selected through stratified random and snowball sampling. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to assess measurement validity, structural relationships, and mediation effects. The results show that trust, regulation, and digital access positively and significantly influence investor behavior, while risk perception has a positive but significant impact. Psychological empowerment was found to partially mediate the relationship between all independent variables and investor behavior, indicating that confidence, autonomy, and self-efficacy enhance the translation of external conditions into active investment. These findings highlight the importance of strengthening regulatory clarity, enhancing platform security, expanding digital access, and fostering investor empowerment to promote responsible and sustainable cryptocurrency participation in Indonesia.